2017
DOI: 10.1016/j.ceramint.2017.01.154
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing and mechanical characterization of high density fully stabilized zirconia

Abstract: Mechanical properties of additively manufactured 8 mol% yttria-stabilized zirconia (8YSZ) parts were extensively studied for the first time. A novel freeform extrusion fabrication process, called Ceramic On-Demand Extrusion (CODE), was employed to deposit an aqueous viscous suspension (~50 vol% solids loading) of fully stabilized zirconia powder in a layer-by-layer fashion. Each layer was exposed to infrared radiation after deposition to attain partial solidification due to drying. Before exposure, the layer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…55,56 It's widely used as a thermal barrier coating, selective laser sintering, gas sensor, polymer membrane filler, structural components, solid electrolytes, and medical application. 59,60 Since 1960, numerous research and development highlighted the YSZ electrolyte fabrication via process yttria oxide doped to zirconia. 59,60 Since 1960, numerous research and development highlighted the YSZ electrolyte fabrication via process yttria oxide doped to zirconia.…”
Section: Current Status Of Yttria-stabilized Zirconia (Ysz)mentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 It's widely used as a thermal barrier coating, selective laser sintering, gas sensor, polymer membrane filler, structural components, solid electrolytes, and medical application. 59,60 Since 1960, numerous research and development highlighted the YSZ electrolyte fabrication via process yttria oxide doped to zirconia. 59,60 Since 1960, numerous research and development highlighted the YSZ electrolyte fabrication via process yttria oxide doped to zirconia.…”
Section: Current Status Of Yttria-stabilized Zirconia (Ysz)mentioning
confidence: 99%
“…57,58 Usually, this ceramic material is used in cubic or tetragonal form and stabilized with aliovalent cations like calcium (Ca 2+ ) and yttria (Y 3+ ) to become a good O 2conductor because of high mechanical strength, high chemical stability, high corrosion resistant, high ionic conductivity, high thermal barrier and low thermal conductivity properties. 59,60 Since 1960, numerous research and development highlighted the YSZ electrolyte fabrication via process yttria oxide doped to zirconia. The introduction of yttria oxide increases the concentration of oxygen vacancies, which improve the crystallographic of electrolyte with increase the mobility of proton inside the YSZ and reduce the energy loss because of the lowering ohmic resistance on solid electrolyte, as presented in Figure 2.…”
Section: Current Status Of Yttria-stabilized Zirconia (Ysz)mentioning
confidence: 99%
“…The CODE process has been shown to be able to produce large complex parts (up to tens ofcentimeters) with near theoretical density (>98%) and a uniform microstructure. Other extensive studies [50][51][52] demonstrated capabilities of CODE to produce mechanically strong parts from different materials.Other advantages include facile preparation of feedstock, low amount of binder content expediting the post-processing, feasibility of embedding sensors [53], andthe capability of grinding products in the green state.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while most ceramics have inherently brittle behavior, the plasticity behavior of structural ceramics has already become the subject of considerable interest [12], and dislocation configurations have been observed after indentation, scratch, and high-rate deformation processes [13][14][15]. However, for additive-manufactured ceramics, mechanical evaluation has been limited to static hardness, flexural strength, and fracture toughness [10,[16][17][18]. The defects of additive-manufactured ZTA ceramics, which can initiate complete failure of the microstructural integrity, usually originate with localized deformation or damage during biomedical service processes [19].…”
Section: Introductionmentioning
confidence: 99%